(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The health system is least prepared to manage sexual dysfunctions and lacks trained professionals who can adequately assess and manage individuals with sexual dysfunctions because the need for the service has not been documented. This is because routine data are not collected on sexual dysfunctions. This study aimed to outline the distribution of sexual dysfunctions among patients seeking health services in a specialized sexual medicine clinic in Nairobi (Sexology Clinic). Methods: Records of all patients seen at the clinic for 12 months were analyzed. A total of 396 patient files were reviewed (362 males and 34 females) using a standard tool. The sociodemographic and medical details of the patients were analyzed. Data were entered in SPSS and summarized using tables and figures. Disease associations with sociodemographic characteristics were analyzed. Classification of sexual disorders was performed using the International Classification of Diseases (ICD)-11. Results: The most prevalent sexual disorders in both genders were sexual arousal disorders (76.4%), sexual desire problems (16.42%), and orgasmic disorders (3.6%). Disease distribution was found to be dependent on patient age and sex. Ethnicity, religion, and profession did not affect disease distribution. Conclusion: The distribution of sexual dysfunctions observed in Nairobi was found to be similar to those observed in other populations. Recommendation: Health promotion and treatment programs for sexual dysfunction should be developed to mirror those in more liberal countries because sexual medicine needs are the same. The health system should collect routine sexual health data to help with future planning.